2010
DOI: 10.1002/jrsm.3
|View full text |Cite
|
Sign up to set email alerts
|

A method for evaluating research syntheses: The quality, conclusions, and consensus of 12 syntheses of the effects of after‐school programs

Abstract: Like all forms of empirical inquiry, research syntheses can be carried out in ways that lead to more or less valid inferences about the phenomenon under study. This synthesis of syntheses (a) examined the methods employed in the syntheses of the effects of after-school programs (ASPs) and determined how closely they conformed to what is defined as best practice for research synthesis, (b) compared the inferences drawn from the ASP research literature by each synthesis with the inferences that plausibly could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…Although researchers, practitioners, and policy makers currently use SR, work continues on how to promote and evaluate the quality of the reviews themselves (Moher et al , ; Moseley et al , ; Valentine et al , ); and, as noted above, one characteristic of quality in SR is the comprehensiveness of the literature searches. Furthermore, although computer searching is not the only component of comprehensive literature searches, it typically serves a core function (Torgerson, ; Petticrew & Roberts, ; Littell et al , ; Lefebvre et al , ; Hammerstrøm et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers, practitioners, and policy makers currently use SR, work continues on how to promote and evaluate the quality of the reviews themselves (Moher et al , ; Moseley et al , ; Valentine et al , ); and, as noted above, one characteristic of quality in SR is the comprehensiveness of the literature searches. Furthermore, although computer searching is not the only component of comprehensive literature searches, it typically serves a core function (Torgerson, ; Petticrew & Roberts, ; Littell et al , ; Lefebvre et al , ; Hammerstrøm et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Within social work, some commonly used words that differ between British and North American spellings include programme/program, behaviour/behavior and counselling/counseling. Moreover, while it might seem obvious, search strategies need be able to take account of linguistic and spelling differences as well as including both abbreviations and fully spelt-out versions of terms (Valentine, Cooper, Patall, Tyson, & Robinson, 2010).…”
Section: Search Methods and Data Retrievalmentioning
confidence: 99%
“…Another common criterion for determining inclusion or exclusion is when a study was first published (Valentine et al, 2010). For example, changes over time in the social policy context, including legislation, policies, and institutional processes can all impact on the effectiveness of interventions (Higgins et al, 2013;Shlonsky & Mildon, 2014).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Borenstein et al [3] reported that meta-analysis, with the property of post-hoc analysis, can reveal the trend of the present study and suggest future research directions. Numerous studies have been performed to evaluate the quality of meta-analyses and systematic reviews following the release of Assessment of Multiple Systematic Reviews (AMSTAR) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist reporting guidelines [4567]. Many researchers have studied and reported on the quality of meta-analyses in the fields of pharmacology and medicine.…”
Section: Introductionmentioning
confidence: 99%